Potential neurotoxic effects of polymethylmethacrylate during cranioplasty. Issue 1 (January 2015) - Pikis, Stylianos; Goldstein, Jacob; Spektor, Sergey
Abstract Cranioplasty for the surgical correction of cranial defects is often performed using polymethyl methacrylate (PMMA), or bone cement. Immediately prior to PMMA application, a liquid monomer form (methylacrylate) and a benzoyl peroxide accelerator are mixed resulting in polymerization, an exothermic reaction during which monomer linking and subsequent formation of solid polymer occur. The potential side effects of residual methylacrylate monomer toxicity and thermal damage of neural tissue during PMMA hardening have been described in various in vitro, animal, and cadaveric studies; however, clinically documented in vivo neurotoxicity in humans attributed to either of the above two mechanisms during PMMA cranioplasty is lacking. We present a series of four patients operated for removal of cerebellopontine angle lesions and two operated for the excision of parieto-occipital tumors who sustained cranial neuropathies and encephalopathies with transient or permanent neurological deficits that could not be attributed to surgical manipulation. We hypothesize that these complications most likely occurred due to thermal damage and/or chemical toxicity from exposure to PMMA during cranioplasty. Our case series indicates that even small volumes of PMMA used for cranioplasty may cause severe side effects related to thermal damage or to exposure of neural tissue to methylacrylate monomer.